2004
DOI: 10.1093/oxfordjournals.schbul.a007079
|View full text |Cite
|
Sign up to set email alerts
|

Direct Costs of Schizophrenia and Related Disorders in Italian Community Mental Health Services: A Multicenter, Prospective 1-Year Followup Study

Abstract: The behavior that accompanies schizophrenia and related disorders interferes with professional and social activities. As a result, schizophrenia is one of the most costly psychiatric illnesses. Direct medical costs associated with schizophrenia were estimated from the Italian National Health Service perspective. This was a multicenter observational 1-year study conducted in 14 Italian community mental health centers (CMHCs). Eligible patients were those with a diagnosis of schizophrenia or schizoaffective or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…This has been noted in the international literature [14] and contrasts with the outcomes of studies in which patients and relatives were interviewed. For example, both a Spanish [30] and an Italian study [17] have estimated that three out of four patients with schizophrenia are excluded from the job market (jobless, on sick leave or on early retirement). The use of surveys with samples that are representative of the population with mental illness and the comparison of their income and employment rates adjusted for age and gender to the working population provide information that more closely reflects the reality of lost productivity due to morbidity than the official registers.…”
Section: Discussionmentioning
confidence: 99%
“…This has been noted in the international literature [14] and contrasts with the outcomes of studies in which patients and relatives were interviewed. For example, both a Spanish [30] and an Italian study [17] have estimated that three out of four patients with schizophrenia are excluded from the job market (jobless, on sick leave or on early retirement). The use of surveys with samples that are representative of the population with mental illness and the comparison of their income and employment rates adjusted for age and gender to the working population provide information that more closely reflects the reality of lost productivity due to morbidity than the official registers.…”
Section: Discussionmentioning
confidence: 99%
“…8 This percentage was multiplied by the average of the disability compensations paid by the National Social Security Institute in Italy. 36 More specifically, only the disability pensions-and not the attendance allowance or incapacity pensions paid by the State or other forms of financial support-were included.…”
Section: Model Structurementioning
confidence: 99%
“…1 In fact, it is estimated that the unemployment rate of patients with schizophrenia is more than double than that of the general population, 8 9 and 51% of them receive a disability pension in Italy. 8 As a consequence, indirect costs are a key aspect to estimate the overall impact of schizophrenia due to the precocity and chronic course of the illness, arising in most cases during adolescence. 10 Furthermore, it is fundamental to efficiently allocate the economic resources in the therapeutic area.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the use of inpatient facilities is a significant component of the cost of treating schizophrenia 55,59. In a review of cost-of-illness studies for schizophrenia, Knapp et al49 found that hospitalization accounted for between 16.5% and 94% of costs, depending on the country and study methods, with two-thirds of the studies finding that hospitalization accounted for more than 50% of total direct health care costs.…”
Section: Health Care Resource Usementioning
confidence: 99%
“…Medications also account for a significant, but substantially lower, proportion (2.0%–13.0% in Western countries) of direct health care costs compared with inpatient and outpatient services 49,59. One study in Zhejiang province reported that the overall cost of hospitalization was ¥10,765 for schizophrenia, with ¥834 for psychiatric medications and ¥719 for nonpsychiatric medication 29.…”
Section: Health Care Resource Usementioning
confidence: 99%